Functional Abnormalities of Cerebellum and Motor Cortex in Spinal Muscular Atrophy Mice. (1st January 2021) - Tharaneetharan, Arumugarajah; Cole, Madison; Norman, Brandon; Romero, Nayeli C.; Wooltorton, Julian R.A.; Harrington, Melissa A.; Sun, Jianli
Highlights: Our data provide the first report of functional neuronal defects in the motor cortex and cerebellum in an SMA mouse model. The observed differences were dependent on both brain region and developmental stage. Spontaneous firing and network activity were significantly lower in the cerebellum but not in the motor cortex. The excitability and synaptic transmission of the output neurons in both cerebellum and motor cortex were altered. Our study suggests the impairment of motor control outputs from these two brain regions in SMA mice. Abstract: Spinal muscular atrophy (SMA) is a devastating genetic neuromuscular disease. Diffuse neuropathology has been reported in SMA patients and mouse models, however, functional changes in brain regions have not been studied. In the SMNΔ7 mouse model, we identified three types of differences in neuronal function in the cerebellum and motor cortex from two age groups: P7-9 (P7) and P11-14 (P11). Microelectrode array studies revealed significantly lower spontaneous firing and network activity in the cerebellum of SMA mice in both age groups, but it was more profound in the P11 group. In the motor cortex, however, neural activity was not different in either age group. Whole-cell patch-clamp was used to study the function of output neurons in both brain regions. In cerebellar Purkinje cells (PCs) of SMA mice, the input resistance was larger at P7, while capacitance was smaller at P11. In the motor cortex, no difference was observed in the passive membrane properties of layer V pyramidal neurons (PN5s). The action potential threshold of both types of output neurons was depolarized in the P11 group. We also observed lower spontaneous excitatory and inhibitory synaptic activity in PN5s and PCs respectively from P11 SMA mice. Overall, these differences suggest functional alterations in the neural network in these motor regions that change during development. Our results also suggest that neuronal dysfunction in these brain regions may contribute to the pathology of SMA. Comprehensive treatment strategies may consider motor regions outside of the spinal cord for better outcomes.